Market Shockwaves: The Impact of Russia-Ukraine Invasion on Oil and Gas Stocks In ASEAN - Pratama, Kevin; Musviyanti (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This Research analyzes market reactions to the Russian invasion of Ukraine, focusing on oil and gas sector stocks in ASEAN markets. The primary variable analyzed is the cumulative abnormal return (CAR) as the dependent variable, with return on equity (ROE) and return on assets (ROA) as independent variables. The data includes all oil and gas sector stocks listed on ASEAN exchanges, selected through purposive sampling based on specific criteria. Analysis methods include paired sample t-test and multiple linear regression. The findings indicate that there was a positive abnormal return on pre-event and event days across all ASEAN countries. However, on post-event days, positive abnormal returns were only seen in Vietnam, Indonesia, Thailand, the Philippines, and Singapore, while Malaysia experienced a negative abnormal return. The abnormal return at 3 days, 2 days, 1 day before and  1 day, 2 days, 3 days after the event is significantly lower than on the event day. The results showed that ROE has a significant positive effect on CAR, while ROA has a significant negative effect on CAR. The negative influence of ROA is attributed to high corporate debt, which became a concern for investors amid geopolitical events